CAT Tool on Teaching Translation for EFL Students - Mafulah, Siti; Tunggal Rahayu Wilujeng, Trisno; Lutviana, Rizky; Hariyanto, Sugeng; Purnawati, Maria; Rahutomo, Faisal (International Journal of Engineering and Technology, 2018)
Teaching translation for EFL Learners is not merely depends on the studentâ€™s linguistics competence but also depends on the background knowledge and how far students understand translation competence as well as the use of technology in translation aspect. This paper aims to depict the use of CAT tool in translation class, some problems faced by the students among translating informative text and the translation error made by the students. The data gathered from the classroom activities on translation class which was followed by 32 students while the instrument used in this research were observation and questionnaire. The findings showed thatÂ overall the class run well, while the problem faced by the students were difficulties in understanding unfamiliar words and they got difficulties in restructuring the text in TL. It is suggested to the beginner translators to do proofreading to make sure that the TL is readable. Â